STRATEGIC DEVELOPMENT OF MODERN BUSINESS IN THE CONDITIONS OF DIGITALIZATION AND EUROPEAN INTEGRATION - Матросова, Людмила; Кононенко, Яна (SWorldJournal, 2024)
The article considers that the joint adaptation and implementation of the European experience of digitalization of the economy in Ukrainian business can be a guarantee of ensuring further sustainable development and increasing the global competitiveness o